Penguatan UMKM Berbasis Ekonomi Hijau Syariah dalam Mewujudkan Pembangunan Berkelanjutan melalui Peran Filantropi Islam - Nabila Aulia Syahrani; Robiatul Al Dawiyah; Ellysa Agustin; Maya Panorama (Li Falah: Journal of Islamic Economics and Business, 2026)
Strengthening Micro, Small, and Medium Enterprises (MSMEs) that rely on Islamic green economy principles is a crucial step toward achieving sustainable development in Indonesia. This study aims to evaluate the role of the Islamic green economy in MSME development and examine the contribution of Islamic philanthropy instruments such as zakat, infaq, sadaqah, and waqf in supporting the sustainability of these businesses. The methodology applied is a qualitative approach through a literature study with descriptive analysis of various related sources. The findings indicate that integrating maqashid al-shariah principles with the green economy can encourage MSMEs to become more environmentally friendly, socially just, and sustainable. In addition, Islamic philanthropy serves as an alternative financing mechanism that can enhance MSME capacity in an inclusive and sustainable manner. Therefore, collaboration between the Islamic green economy and Islamic philanthropy can become a strategic solution to strengthen MSMEs while supporting the achievement of the Sustainable Development Goals (SDGs). The results of this study are expected to serve as a reference for governments, MSME actors, and Islamic philanthropic institutions in developing MSME empowerment strategies focused on economic, social, and environmental sustainability.